Corynebacterium bouchesdurhonense sp. nov., and Corynebacterium provencense sp. nov., two new species isolated from obese patients - Lo, C.I. (New Microbes New Infect, 2019)
Corynebacterium bouchesdurhonense sp. nov. strain Marseille-P2067(T) (= CSURP2067; = DSM100846) and Corynebacterium provencense sp. nov. strain Marseille-P2161(T) (= CSURP2161; = DSM101074) are two new species from the order Corynebacteriales that were isolated from obese French individuals.